Epidemiology of asthma exacerbation in children before and after the COVID-19 pandemic: a retrospective study in Chengdu, China - Lei Zhang; Hanmin Liu; Tao Ai; Zijin Chen; Wei Tang; Shuai Hu; Jie Hu (BMC, 2023)
Abstract Purpose To examine the numbers and characteristics of children affected by asthma exacerbation in Chengdu, China, before and after the COVID-19 pandemic to inform efforts to manage childhood asthma in the post epidemic era. Methods Data were retrospectively collected from children admitted for asthma exacerbation to Chengdu Women and Children's Central Hospital between January 2017 and December 2022. Rates of hospitalization, ages of the affected children, comorbidities and infections, and relationships between hospitalization and seasonal or environmental factors were examined before and after the epidemic. Results Fewer children were hospitalized for asthma exacerbation, yet more hospitalized children had severe exacerbation after the epidemic than before. Rates of hospitalization varied considerably with time of year, and the timing of peak hospitalizations differed before and after the epidemic. Only before the epidemic, rates of hospitalization for asthma exacerbation were positively correlated with humidity. Infants made up a smaller proportion of hospitalized children after the epidemic than before, with preschool children accounting for most hospitalizations after the epidemic. The proportion of children hospitalized for asthma exacerbation who also had pneumonia was significantly smaller after the epidemic than before. Conversely, the proportion of children hospitalized for asthma exacerbation who also had allergic diseases was significantly greater after the epidemic than before. Conclusion The epidemiology of asthma exacerbation in children changed after the epidemic. Future efforts to manage the condition in the paediatric population should focus on severe asthma exacerbation, prevention and management of allergic diseases, and the influence of meteorological and environmental factors.